Feasibility Study of Po Kebumen Cattle Breeding and Fattening Business Management - nuraeni , Nunur; Faisal Ismail Aryadi, Muhammad (Bulletin of Applied Animal Research, 2022)
Kebumen regency is one of the local beef cattle breeding centers, especially cows from Peranakan Ongole (PO) san have their own line of cattle, PO 's cow Kebumen. PO 's cow population in Kebumen District has decreased from 2010 until 2015. Through the activities of the Regional Excellence Research (Riset Unggulan Daerah), the government tries to conduct feasibility study on the management of livestock business in Kebumen. The purpose of this study is to determine the factors / aspects that are required in the establishment of Livestock Business with legal status, knowing whether or not the establishment of Livestock Business with Legal Entity in Kebumen Regency and produce Model Operationalization of Management of Livestock Business with legal . Based on the results of primary and secondary data processing recommendation of business entity management of breeding and fattening PO 's cow Kebumen is a Regional Company and if the Regional Company long enough in its establishment can be initiated by the Business of Cultivation and Feeding PO 's Cow Kebumen (BUMDES) in nursery location. The pattern of business management both implemented by Perusda and Bumdes is divided into three maintenance patterns namely a) maintenance by perusda, b) maintenance by way of whereby all the assets are still owned by breeders and c) maintenance in a manner where all the asset of female seeds belonging to the farmer / plasma . Based on the calculation of financial analysis on each pattern shows the NPV value of pattern A and B positive is Rp. 12,039,167,898,26 and Rp. 3,035,475,194,15, whereas in pattern C the negative value is Rp. (4,668,450,161,29). The Net B / C calculation on maintenance pattern A is 1.2 on maintenance B 1.16 and in the maintenance pattern C 0.96. The IRR value shows greater value than Discount Factor (> 20%) on maintenance pattern A, B and C respectively 55.73, 46.71 and 46.71. Payback Period (PP) value in maintenance pattern A showed the fastest return time of 2.55 years or less than five years, whereas in the pattern of maintenance B and C showed the number of more than five years of 5.26 years. Based on these data, the maintenance pattern of A and B is feasible to run in establishing perusda the Breeding and Fattening PO's Cow Kebumen, while the C pattern was not feasible. Pattern B was preferable to run because in addition to the development, the preservation of PO Kebumen Cattle, increase livestock activities in Kebumen District and increase PAD can also prosper the farmers community. Keywords: Breeding, Fattening, PO's Cow Kebumen , Regional Company